2003
DOI: 10.1093/hmg/ddg349
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in frataxin causes progressive accumulation of mitochondrial damage

Abstract: Frataxin protein controls iron availability in mitochondria and reduced levels lead to the human disease, Friedreich's ataxia (FRDA). The molecular aspects of disease progression are not well understood. We developed a highly regulatable promoter system for expressing frataxin in yeast to address the consequences of chronically reduced amounts of this protein. Shutting off the promoter resulted in changes normally associated with loss of frataxin including iron accumulation within the mitochondria and the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 66 publications
4
68
0
Order By: Relevance
“…In yeast, it was demonstrated that frataxin is involved in mitochondrial iron efflux (252) or iron storage (96,234). Turning off the yeast frataxin promoter in an inducible system caused accumulation of iron in mitochondria and resulted in mitochondrial and nuclear oxidative DNA damage (153). The frataxin-deficient yeast also showed more production of hydrogen peroxide, higher sensitivity to DNA-damaging agents, and increased chromosomal instability (152), suggesting that detoxification of mitochondrial iron is a primary function of frataxin (97).…”
Section: B Frataxin and Mitochondrial Iron Trafficmentioning
confidence: 99%
“…In yeast, it was demonstrated that frataxin is involved in mitochondrial iron efflux (252) or iron storage (96,234). Turning off the yeast frataxin promoter in an inducible system caused accumulation of iron in mitochondria and resulted in mitochondrial and nuclear oxidative DNA damage (153). The frataxin-deficient yeast also showed more production of hydrogen peroxide, higher sensitivity to DNA-damaging agents, and increased chromosomal instability (152), suggesting that detoxification of mitochondrial iron is a primary function of frataxin (97).…”
Section: B Frataxin and Mitochondrial Iron Trafficmentioning
confidence: 99%
“…Controlling the ability of iron to perform redox chemistry appears to be an additional function of frataxin, suggesting this protein may directly participate in controlling cellular oxidative stress by reducing ROS production. In vivo reports indicate frataxin deficiency leads to oxidative damage in humans (Emond et al, 2000;Schultz et al, 2000), mice (Ristow et al, 2003;Thierbach et al, 2005), yeast (Karthikeyan et al, 2003), and Caenorhabditis elegans (Vazquez-Manrique et al, 2006). Mitochondrial iron overload, resulting from a frataxin deficiency, leads to oxidative damage in mitochondrial and nuclear DNA as well as to Fe-S clusters in mitochondrial aconitase and other respiratory enzymes (Babcock et al, 1997;Foury, 1999;Karthikeyan et al, 2002).…”
Section: Frataxin Controls Iron's Redox Chemistrymentioning
confidence: 99%
“…Previous studies reported the defective respiration, unstable mitochondrial DNA, and hypersensitivity to oxidative stress that follow inactivation of the yeast frataxin homologue (Yfh1) (6,20). The impairment of mitochondrial iron metabolism, particularly FeS cluster and heme synthesis, was suggested to be the primary cause for this complex phenotype (48).…”
Section: Complementation Of Yeast Frataxin Mutantsmentioning
confidence: 99%